Impact of Income and Renewable Energy on Carbon Emissions: Evidence from Middle East Countries - Abdulraqeb, Omar Ahmed; Erbao, Cao; Aloqab, Abdullah; Abdulla, Al-Dakhli (iRASD Journal of Economics, 2024)
Most Middle East countries mainly depend on natural resources and energy sector is almost responsible for one-third of its environmental degradation. Most Middle East countries are going for greener energy and at the same time maintaining their economic growth. Henceforth, this study examines the effects of income and renewable energy on degradation of environment. Furthermore, total natural rent, trade openness, and urbanization are control variables in this panel study. The main aim of the study is to investigate in the Middle East the influence of several elements like total natural resource rents, urbanization, trade openness, and renewable energy and income on CO2 emissions. Panel techniques and tests such as cross-sectional dependency, panel unit root test, Westerlund panel cointegration test and FMOLS. This study finds that urbanization, trade openness, income, and total natural rent degrade environmental quality, whereas renewable energy improves environmental quality in Middle East Countries. It is recommended that policymakers incorporate environmental considerations into development plans. It is also recommended that Middle East countries enhance the share of renewable energy sources and improvement in natural resource management as most middle countries rely largely on natural resource revenues.